Nutrition Awareness Counseling to Support Indonesia Ready for New Normal - Latifahtur Rahmah; Irra Chrisyanti Dewi; Ryan Yeremia Iskandar (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
Proper nutrition and adequate water are essential during the COVID-19 outbreak. People who eat a balanced diet tend to be healthier with a stronger immune system. The risk of chronic diseases and infectious diseases is lower, so there needs to be an outreach to the public about nutrition awareness to support Indonesia to be ready for the new normal. Nutrition education serves to create awareness and spread knowledge. The implementation of this counseling consists of the delivery of material and questions and answers. The material consists of: 1) nutrition conscious behavior that focuses on balanced nutrition guidelines and the role of vitamins and minerals in increasing the body's immune system; 2) Nutrition conscious behavior that focuses on the role of essential fats (EPA and DHA) in increasing the body's immune system; 3) Nutrition conscious behavior that focuses on processing food with balanced nutrition. A series of outreach activities have been well organized. Most of the counseling participants felt that community service activities were carried out through counseling about nutrition awareness to support indonesia ready for new normal. This nutrition awareness counseling is very useful to prepare nutrition for the Covid-19 pandemic.